Influence of Internal Structure of the Sorbents on Diazepam Sorption from Simulated Intestinal Fluid - Mircea Stefan; Ioana Stefan; Ioana-Alexandra Negoita; Viorel Ordeanu; Daniela Simina Stefan (Applied Sciences, 2021)
The capacity of natural Na-montmorillonite and activated charcoal for sorption of diazepam from simulated intestinal fluid (SIF) was studied. The main characteristics of the sorbents were determined. In order to characterize the sorption process of diazepam the influence of the pH, contact time and ethanol presence in SIF was analyzed. Adsorption isotherms for the diazepam-activated charcoal and diazepam-natural Na-montmorillonite systems were determined. The Langmuir isotherm model provided a very good description of diazepam sorption. Furthermore, the pH-drift method was used to determine the specific pH at zero point of charge (pHzpc) of the sorbents. The obtained results show that the internal structure of the sorbents and pH of the SIF solutions are very important for diazepam sorption. Both the surface of the activated charcoal and natural Na-montmorillonite are positively charged below the pHzpc so the sorption of diazepam is higher below this point and occur by van der Waals forces. The presence of ethanol in simulated intestinal fluid lowers the adsorption of diazepam on both sorbents.